A multidimensional representation of the consumer under industry 4.0 and social manufacturing - Barbosa, Ricardo (2021)
Organisations face a new challenge that results from the increasing demand for customised products, motivated by trends that can quickly shift. The inclusion of the consumer in the manufacturing processes (Social Manufacturing) also raises new challenges regarding their representation. Based on three consumer satisfaction categories: (1) Perceived Value; (2) Consumer Expectation; (3) Consumer Loyalty; this work proposes a multidimensional representation of the consumer in three dimensions: (1) Personalisation; (2) Opinion; (3) Engagement. This model is based on the definition of complex networks, and the multidimensional aspect allows organisations to isolate and combine different dimensions to better understand their consumers, their opinions, and their demands for new products. The multidimensional characteristic of the model, namely the isolation and combination of dimensions, can help organisations understand if common customisation demands share common background, understand what demands should be addressed or prioritised, or even anticipate trends.